1995
DOI: 10.1272/jnms1923.62.186
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of so-called keloid with excision and postoperative electron irradiation.

Abstract: Between 1988 and 1994, 110 patients with 139 so-called keloids site, which had been treated with conservative therapy were treated with excision, suture, and postoperative irradiation with a 4 MeV electron beam. They were irradiated within one or two days after surgery, for three consecutive days. The total doses were 15 Gy or 18 Gy per fractions for the most part. Control rates of true keloids and hypertrophic scars were 76.0% (57/75) and 93.8% (60/64), respectively, and the overall effectiveness rate was 84.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Thus, a 15 Gy dose was chosen for the cDNA microarray analyses. In addition, a comparable dose has been effectively used in several clinical and experimental studies to prevent keloid recurrences (Lo et al, 1990;Mitsuhashi and Miyashita, 1995;Maarouf et al, 2002;Ogawa et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, a 15 Gy dose was chosen for the cDNA microarray analyses. In addition, a comparable dose has been effectively used in several clinical and experimental studies to prevent keloid recurrences (Lo et al, 1990;Mitsuhashi and Miyashita, 1995;Maarouf et al, 2002;Ogawa et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Although simple excision and closure result in a recurrence rate of more than 50%, several studies have shown that surgery associated with post-operative EB irradiation provide more than 70% success rate in prevention or recurrence of keloids (Lo et al, 1990;Mitsuhashi and Miyashita, 1995;Ogawa et al, 2003). The molecular mechanism(s) behind the effect of EB irradiation has, however, not been explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to a dose of 15 Gy, irradiation given to the patients after surgical excision of hypertrophic scars successfully prevented hypertrophic scars or keloids formation and recurrence. [24] Relative lower recurrence rate was also reported after technology mainstay transition[2526] among Asians with keloids. Later, high-dose-rate (HDR) brachytherapy provided us with an alternative external radiation therapy, particularly for patients who are resistant to adjuvant external beam radiation therapy or corticosteroids, which resulted in a recurrence rate ranging from 4.7% to 21%.…”
Section: History and Overview: From Superficial X-ray Irradiation To mentioning
confidence: 90%
“…The KFs and NFs had been characterized in terms of the cell growth and collagen synthesis properties as reported previously 32. Early passages 4-7 of cells were cultured in Dulbecco's modified Eagle's medium (DMEM), supplemented with 10% fetal calf serum, penicillin (100 IU/ml), streptomycin (100μg/ml), and amphotericin B (0.25μg/ml) at 37C in a humidified 5% CO2 incubator. The cultures were maintained until reaching 70 to 80% confluence.…”
Section: Methodsmentioning
confidence: 99%